2xy*9 if x=3 and y = 2 2(3)(2)*9 12*9 108 You substitute x and y for their equivalent (3 and 2) then simply multiply 2*x*y, then multiply the answer of that by 9.
√18xy = √(9*2xy) = √9*√2xy = 3*√(2xy)
2xy + 6 = 4xyz Divide through by 2: xy + 3 = 2xyz 3 = 2xyz - xy = y*(2xz - x) Therefore, y = 3/(2xz - x) provided that 2xz - x is not zero.
Yes, x = 2 is the solution.
(2x2+4xy-3)-(x2-2xy-4)Answer: x2+6x+1
2xy substitute 3 for y and 5 for x 2(5)(3) = 30
2xy*9 if x=3 and y = 2 2(3)(2)*9 12*9 108 You substitute x and y for their equivalent (3 and 2) then simply multiply 2*x*y, then multiply the answer of that by 9.
√18xy = √(9*2xy) = √9*√2xy = 3*√(2xy)
That equals 2xy + 3y which factors to y(2x + 3)
2xy + 6 = 4xyz Divide through by 2: xy + 3 = 2xyz 3 = 2xyz - xy = y*(2xz - x) Therefore, y = 3/(2xz - x) provided that 2xz - x is not zero.
Yes, x = 2 is the solution.
the difference between 2x2 +4xy-3 and x2-2xy-4 is?
Yes. It is THE solution.
Assuming y' is dy/dx, y = x^4/4 + yx^2
(x^2 + 2y)(x^3 - 2xy + y^3) = x^2(x^3 - 2xy + y^3) + 2y(x^3 - 2xy + y^3) Now, let's distribute each term: = x^2 * x^3 - x^2 * 2xy + x^2 * y^3 + 2y * x^3 - 2y * 2xy + 2y * y^3 Now, simplify each term: = x^5 - 2x^3y + x^2y^3 + 2x^3y - 4xy^2 + 2y^4 Now, combine like terms: = x^5 + x^2y^3 - 4xy^2 + 2y^4 So, the expanded form of (x^2 + 2y)(x^3 - 2xy + y^3) is x^5 + x^2y^3 - 4xy^2 + 2y^4.
if y = 2- x then x^2 + 2x(2 - x) = 3 ie x^2 + 4 x -2x^2 = 3 ie 4x - 3 = x^2 x^2 - 4x +3 = 0 = (x - 1)(x - 3) so x = 1 or 3 Check: y= 2 - 1 =1; x^2 = 1, 2xy = 2 x 1 x 1 = 2, 1 +2 = 3. y = 2 - 3 = -1; x^2 = 9, 2xy = 2 x 3 x -1 = -6, 9 + -6 = 3. QED.
no.. x equals 11